PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN TERHADAP HASIL BELAJAR PKN SISWA SMP NEGERI 1 DAN 2 GEDANGAN SIDOARJO YANG MEMILIKI TINGKAT MOTIVASI BELAJAR YANG BERBEDA: Pembelajaran inkuiri, pembelajaran ekspositori, motivasi belajar, hasil belajar - Suyono, Suyono (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2010)
Inquiry teaching and learning strategies and motivation to learn expository part Civics affecting learning outcomes that will be examined in this study. While the purpose of this study to determine whether there are differences in student learning outcomes PKn Class VIII and SMP Negeri 1 SMP Negeri 2 Sidoarjo between following the strategy of learning by inquiry and expository learning, to find out whether there are differences in learning outcomes between students who have high motivation and student learning who have low motivation to learn and to learn about the interaction between learning strategies with the motivation to learn the results of Class VIII studying PKn and SMP Negeri 1 SMP Negeri 2 Sidoarjo. This type of research is research used four classes of experiments and study sample. The sampling technique is a type of probability sampling with simple Random sampling. Analysis of data using the formula Anova Two Line for the first hypothesis found the price F of 12.997 and a significance of 0.000 for the second hypothesis found the price F of 56.596 and a significance of 0.000 for the third hypothesis use the statistical technique Anova Two Line found the price F of 1.738 and a significance of 0, 028. Thus the conclusion can be drawn that: (1) there are differences in student learning outcomes PKn Class VIII and SMP Negeri 1 SMP Negeri 2 Sidoarjo between following the strategy of learning by inquiry and expository learning, (2) there is a difference between learning outcomes that have a high motivation to learn and which has a low learning motivation (3) there is an interaction between learning strategies with the motivation to learn the result of Class VIII studying PKn and SMP Negeri 1 and SMP Negri 2 Sidoarjo.